Existing Problems in Attracting Foreign Investments to the National Economy (Eurasian Journal of History, Geography and Economics, 2023)
The importance of foreign investments and their role in the development of the national economy was highlighted and analyzed based on statistical data. Also, the article describes in detail the existing problems in attracting foreign investments to the national economy and what measures should be used to activate their prevention.